Maternal Outcomes of Breastfeeding in King Abdulaziz University Hospital, Saudi Arabia - Lama A. Banjar; Hanan M. Faruqui; Afaf H. Ghunaim; Amal F. Almalki; Haifa M. Alshaikh; Mashael Alsamti; Hala H. Mosli (Journal of King Abdulaziz University: Medical Sciences, 2023)
Breastfeeding has a great efficacy on the growing infant, as well as the mother. It has been suggested that breastfeeding promotes postpartum weight loss. Furthermore, it may alter the risk of developing postpartum depression. The aim of this study is to further understand the adherence and the effect of breast milk feeding on developing a postpartum depression and calculating the postpartum weight reduction percentage in comparison to pre-pregnancy weight. A cross-sectional study was conducted in King Abdulaziz University Hospital among 153 mothers, whose infants are less than two years of age. Data were collected by interviewing the mothers using a standard questionnaire designed for the study and the HAMD depression scale with anthropometric measures. 85.62% of the study sample had breastfed, 43.38% breastfed for 1 to 2 months, and 24.18% for 6 months or more. However, the relationship of postpartum depression and breastfeeding was not significant with a P-value > 0.05. 84.97% of the included mothers had the same or greater weight than before pregnancy. In conclusion, mothers in King Abdulaziz University Hospital are well adherent to breast milk feeding. The association of breastfeeding to weight loss was not observed as suggested. Mothers with postpartum depression were less adherent to the practice of breastfeeding.